The test-retest reliability of a 16.1 km time trial in trained cyclists using the Wattbike Pro ergometer in hot environmental conditions - Dobson, B.; Tinnion, D. J.; Gough, L. A.; McNaughton, L. R.; Sparks, S. A. (Journal of Science and Cycling, 2025)
The Wattbike Pro ergometer (Wattbike) is readily available and widely used by athletes, coaches, and researchers as a tool for cycling performance assessment. To-date, no literature has reported the test-reliability of relevant performance criterion using the Wattbike and a 10-mile (16.1 km) TT - which is the most prevalent race distance, often completed in the summer race season. Therefore, the aim of this study was to assess the reliability of 16.1 km TT performance in the heat using the Wattbike Pro ergometer. A cohort of trained cyclists volunteered to take part in this study (n = 16, mean ± SD age 36.4 ± 14.0 y, height, 1.77 ± 0.09 m, body mass 75.2 ± 7.3 kg, PPO 365.1 ± 55.2 W, VO2max 55.0 ± 9.5 mL.kg-1.min-1. Participants performed a familiarisation, prior to two 16.1 km TT on the Wattbike Pro ergometer separated by 3-7 days. Differences in mean completion time, power output, and speed were determined using paired samples T-tests, with quartile data assessed using repeated-measures ANOVA. Reproducibility of the performance measures was performed using the coefficient of variation (CV), intraclass correlations, technical error (rTE and sTE) and, Cronbach`s a. There were no significant differences between TT1 and TT2 for time, power output and speed (mean difference = 3.25 s, 3.2 W, and 0.15 km·h-1, respectively). All performance data demonstrated excellent reproducibility (CV range = 0.8 - 1.9%) with trivial sTE (0.16 - 0.20). The 16.1 km cycling TT when conducted on a Wattbike Pro ergometer demonstrates a very reliable performance criteria in cohorts of trained cyclists, when exercising in hot conditions. Athletes, coaches, and researchers alike, should be aware of the inter-bike reliability which has been previously reported, and ensure that the same ergometer is used when measuring performance, thereby ensuring the reliability of the 16.1 km TT.